Factors affecting the use of mhealth home workout – no equipment application in indonesia with an intention to use approach - Damar Wulan; Ahmad Shalahuddin; Wenny Pebrianti; Ramadania Ramadania; Syahbandi Syahbandi (Institute of Computer Science (IOCS), 2023)
This study's objective is to identify the predictors of usage intention among Indonesia's Generation Z. Mobile health (mHealth) can contribute to Indonesia's public health system. A sample of 375 Generation Z individuals who own a smartphone and have information about the mHealth application